Coherently remapping toroidal cells but not Grid cells are responsible for path integration in virtual agents - Vemund Schøyen; Markus Borud Pettersen; Konstantin Holzhausen; Marianne Fyhn; Anders Malthe-Sørenssen; Mikkel Elle Lepperød (iScience, 2023)
Summary: It is widely believed that grid cells provide cues for path integration, with place cells encoding an animal’s location and environmental identity. When entering a new environment, these cells remap concurrently, sparking debates about their causal relationship. Using a continuous attractor recurrent neural network, we study spatial cell dynamics in multiple environments. We investigate grid cell remapping as a function of global remapping in place-like units through random resampling of place cell centers. Dimensionality reduction techniques reveal that a subset of cells manifest a persistent torus across environments. Unexpectedly, these toroidal cells resemble band-like cells rather than high grid score units. Subsequent pruning studies reveal that toroidal cells are crucial for path integration while grid cells are not. As we extend the model to operate across many environments, we delineate its generalization boundaries, revealing challenges with modeling many environments in current models.